2021
DOI: 10.1111/jen.12866
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal abundance of Tuberolachnus salignus and its effect on flowering of host willows of varying susceptibility

Abstract: The giant willow aphid Tuberolachnus salignus Gmelin is a large phloem‐feeding insect which colonizes the stems of willow trees. This aphid is a new invasive species in New Zealand and there is limited knowledge of its inter‐annual population patterns and the damage it can cause to willow hosts. Our study investigated the T. salignus population dynamics and its effects on the flowering parameters of fifteen willow species and hybrids in a field trial. The aphid population levels were found to vary among the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The depletion of carbohydrate reserves in autumn has been observed with woolly poplar aphid (Phloeomyzus passerinii) infestation of Populus tremuloides, and bark of Populus tremuloides in the autumn, as a result of woolly poplar aphid (P. passerinii) infestation, were associated with reduced stem radial growth of the plants during the following season. The largest reductions in growth during the second season occurred in the cultivars of S. candida and S. viminalis that had large aphid populations; the same plants showed delayed and extended spring flowering, and reductions in flowering catkin size (Tun et al, 2021). By contrast, the S. eriocephala and S. lasiolepis × viminalis cultivars had no reduction in growth during the second season, had small populations of aphids that produced little honeydew (Tun et al, 2020), and showed no delays in spring flowering (Tun et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The depletion of carbohydrate reserves in autumn has been observed with woolly poplar aphid (Phloeomyzus passerinii) infestation of Populus tremuloides, and bark of Populus tremuloides in the autumn, as a result of woolly poplar aphid (P. passerinii) infestation, were associated with reduced stem radial growth of the plants during the following season. The largest reductions in growth during the second season occurred in the cultivars of S. candida and S. viminalis that had large aphid populations; the same plants showed delayed and extended spring flowering, and reductions in flowering catkin size (Tun et al, 2021). By contrast, the S. eriocephala and S. lasiolepis × viminalis cultivars had no reduction in growth during the second season, had small populations of aphids that produced little honeydew (Tun et al, 2020), and showed no delays in spring flowering (Tun et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…The largest reductions in growth during the second season occurred in the cultivars of S. candida and S. viminalis that had large aphid populations; the same plants showed delayed and extended spring flowering, and reductions in flowering catkin size (Tun et al, 2021). By contrast, the S. eriocephala and S. lasiolepis × viminalis cultivars had no reduction in growth during the second season, had small populations of aphids that produced little honeydew (Tun et al, 2020), and showed no delays in spring flowering (Tun et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…and Salix schwerinii E. Wolf in New Zealand. 33 Additionally, Tun et al 34 found that in New Zealand, GWA on Salix fragilis has medium levels of aphid persistence on willows, compared to other species such as Salix viminalis L. This species can persist 30% more time at high levels, suggesting that host-plant nutritional quality could also affect GWA persistence. In our region, GWA appears to have a shorter permanence of willows than other parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible scenario is the interaction between alien invasive plants and insects, which is predicted to increase due to global trade and climate change (Johnson et al, 2009). A series of studies (Tun et al, 2020(Tun et al, , 2021(Tun et al, , 2022Jones et al, 2021) investigated the resistance, growth, reproduction, and VOC emission of 15 introduced willow clones in New Zealand in response to the attack of the giant willow aphid Tuberolachnus salignus (of Asian origin). These willow clones were mainly from Europe and North America, with some having invasive traits.…”
Section: Biotic Factorsmentioning
confidence: 99%